Exploring sustainable alternatives: Utilizing natural precursor for eco-friendly polybenzoxazine - Muhammad Nor Arifin, Yaakob; Nurjannah, Salim; Siti Noor Hidayah, Mustapha; Izan Izwan, Misnon; Mohd Hasbi, Ab Rahim; Rasidi, Roslan (Elsevier Ltd., 2024)
Rising concerns about petrochemical-based materials' sustainability and health risks drive the search for alternatives to natural resources. Polybenzoxazines, known for their exceptional thermal stability, low water absorption, and high glass transition temperature, are promising candidates. However, conventional synthesis relies on petroleum-derived monomers like phenol, raising concerns. This review highlights the vast potential of bio-based polybenzoxazines. Biorefinery advancements and new biosynthetic pathways are paving the way for versatile natural monomers like resveratrol and furfurylamine. These alternatives address sustainability and health concerns while offering comparable, and sometimes even superior, material properties. The review delves into the chemistry and structure of polybenzoxazines, tracing their evolution since 1944. It explores the sources and extraction methods of potential bio-based monomers, showcases their application in resin production, and analyzes technical and economic challenges and opportunities. By promoting sustainable materials development and addressing safety considerations, this review paves the way for bio-based polybenzoxazine resins, contributing to a greener and more sustainable future for materials production.